Future Auditors in the Making: A Socioeconomic Lens on Career Motivation and Tri Nga Principles - Wardani, Dewi Kusuma; Luly, Clarita Virginia Anggi (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to determine the effect of accounting students' perceptions of social factors and understanding of the tri nga teachings on career choices as auditors using quantitative methods. In this study using primary data by distributing questionnaires to students of the accounting study program at Sarjanawiyata Tamansiswa University. The sample collection method uses convenience sampling. Respondent data collected and processed were 104 . With research findings showing that social factors have a positive impact on the choice of a career as an auditor, while the understanding of the tri-nga teachings does not affect the choice of students to pursue a career as an auditor.